Multi-robot informative path planning in unknown environments through continuous region partitioning. (25th November 2020) - Dutta, Ayan; Bhattacharya, Amitabh; Kreidl, O Patrick; Ghosh, Anirban; Dasgupta, Prithviraj
We consider the NP-hard problem of multirobot informative path planning in the presence of communication constraints, where the objective is to collect higher amounts of information of an ambient phenomenon. We propose a novel approach that uses continuous region partitioning into Voronoi components to efficiently divide an initially unknown environment among the robots based on newly discovered obstacles enabling improved load balancing between robots. Simulation results show that our proposed approach is successful in reducing the initial imbalance of the robots' allocated free regions while ensuring close-to-reality spatial modeling within a reasonable amount of time.